Céline - Germain, Georges-Hébert (Éditions Club Québec Loisirs, 1997)
Voici le portrait d'une femme libre, autonome, amoureuse, physiquement et mentalement saine et souple. Céline Dion est portée par une grande ambition, qui n'est pas celle des autres mais la sienne propre, et par ses rêves à elle, que son imprésario, l'homme de sa vie, René Angélil, l'aide à réaliser. L'histoire racontée ici est faite de multiples conquêtes, certaines longues et ardues, d'autres faciles ou imprévues. Certaines de ces conquêtes sont intimes, d'autres sont hautement spectaculaires et médiatisées.

Répertoire des œuvres des compositrices du Québec au XXe siècle - Labelle, Nicole (Centre de recherche en civilisation canadienne-française, 1997)

Emma Albani. La diva, la vedette mondiale - Labrèche-Larouche, Michelle (XYZ, 1997)
La vie de la célèbre cantatrice canadienne-française qui, au XIXe siècle, conquit l’Europe et l’Amérique et fut l’amie de la reine Victoria et de célèbres compositeurs tels Liszt et Brahms.

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation m the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.

Vicissitudes - Maidanik, Victoria (Université McGill, 1997)
Vicissitudes is a composition for orchestra with a duration of approximately 13$ sp prime$ 30$ sp{ prime prime}$. The main idea of the piece, the subdivision of the orchestra into small soloistic groups along with larger ensembles, was inspired by the principles of one of the Baroque forms, namely the Concerto Grosso.

À la manière des préludes non mesurés - Panneton, Isabelle (Circuit : musiques contemporaines, 1997)
Faisant état de l’influence sur elle du répertoire baroque, la compositrice montre quel rôle de modèle ont joué pour elle les préludes non mesurés de Rameau et Couperin, notamment dans son oeuvre Trait, Écart, Réparties. Elle en indique ensuite les prolongements dans quelques autres pièces.

La critique féministe étatsunienne en musique : pertinence en milieu francophone Québécois - Sabourin, Carmen (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)